A Wind Tunnel Experimental Study on the Icing Characteristics of a Cylinder Rotating around a Vertical Axis - Wenfeng Guo (MDPI AG, 2021)
Rotating machinery in cold and humid regions is prone to icing. For exploring the characteristics of icing on objects rotating around a vertical axis, such as vertical axis wind turbines (VAWT), a cylinder rotating around the vertical axis was selected as the research object in this study. Three cylinders with different diameters were selected, and icing tests carried out under different tip speed ratios (TSR) in a self-built icing wind tunnel. The icing characteristics were quantitatively analyzed using characteristic parameters, including the icing area, the dimensionless icing area, the stagnation point thickness and the dimensionless stagnation point thickness. The dimensionless stagnation point thickness decreased with increases in the diameter of the cylinder. The icing limit decreased with an increase in the rotational speed of the cylinder, and reached 50% under the high TSR condition. Various icing characteristics were also analyzed for two rotation modes: rotation around the vertical axis and around the horizontal axis. The research findings in the present study lay the theoretical and experimental foundations for exploring VAWT icing in depth.